Risks of Academic Underachievement in Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
The relation between neuropsychological functioning and academic achievement and the role of family environment, seizures, and psychosocial variables were examined in 173 children with chronic epilepsy, ages 8 to 15 years, at Purdue School of Science; Indiana University School of Medicine, Indianapolis; and University of Wisconsin-Madison School of Medicine, WI.